HIGHER MILITARY EDUCATION: BASIS TO ENSURE AND GUARANTEE THE QUALITY OF MILITARY SPECIALISTS TRAINING - Зельницкий, А. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to the research of the phenomenon of higher military education quality and conceptual basis to ensure and guarantee the quality of military specialists training in higher military educational institutions. This research is based on the results of the pedagogical categories definitive analysis of "education quality "; "assurance education quality ";"guarantee education quality ". There are considered conditions for the inclusion of these categories in the military pedagogy thesaurus. The conditions of their inclusion Discusses the essence; content; communications and relations of pedagogical concepts that are components of these categories. The attention is focused on the study of the pedagogical concept of "professional competence". There is noted the need to develop pedagogical concept of guaranteeing the quality of military specialists training in higher military educational institutions. At this research the following theoretical methods are used: systematic analysis and synthesis of philosophical; psychological and pedagogical sources; compilation and systematization of theoretical knowledge and methods of analogies; idealization; abstraction; allowing to describe more deeply the essence of the phenomenon quality of higher military education and approaches with respect to its security and guarantee